Bipolar resistive switching with negative differential resistance effect in a Cu/BaTiO3/Ag device. Issue 19 (24th April 2017) - Wei, L. J.; Yuan, Y.; Wang, J.; Tu, H. Q.; Gao, Y.; You, B.; Du, J.
Abstract : We demonstrate that a bipolar non-volatile resistive switching behaviour with negative differential resistance (NDR) effect is realized in a Cu/BaTiO3 /Ag device, which was deposited on a Si substrate via magnetron sputtering equipment. Abstract : We demonstrate that a bipolar non-volatile resistive switching behaviour with negative differential resistance (NDR) effect is realized in a Cu/BaTiO3 /Ag device, which was deposited on a Si substrate via magnetron sputtering equipment. We suggest that the bipolar resistive switching is dominated by the trapping/detrapping of electrons at the BaTiO3 –Cu interface. In addition, we demonstrate that the device exhibits good performance, including a large on/off ratio, high reliability and long retention time. Therefore, BaTiO3 may become a good candidate for application in resistive switching random access memory (RRAM) devices.